Photoluminescence properties of PZT 52/48 synthesized by microwave hydrothermal method using PVA with template - Teixeira, G. F. [UNESP]; Gasparotto, G. [UNESP]; Paris, E. C.; Zaghete, M. A. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2012)
Lead Titanate Zirconate (PZT) perovskite powders were synthesized by microwave hydrothermal method (M-H) at 180 degrees C for different time periods (2, 4, 8 and 12 h) with the presence of aqueous polyvinyl alcohol (PVA) solution 0.36 g L-1. The X-Ray diffraction (XRD), SE-FEG as well as the measurements of photoluminescence (PL) emission were used for monitoring the formation of a perovskite phase with random polycrystalline distortion in the structure. Emission spectra with fixed excitation wavelength of 350 nm showed higher value for the powder obtained after undergoing 8 h of treatment. A theoretical model derived from previous calculations allows us to discuss the origin of photoluminescence emission in the powders, which can be further related to the local disorder in the network of both ZrO6 and TiO6 octahedral, and dodecahedral PbO12. The new morphology initially observed from the PZT perovskite crystal growth bearing the shape of fine plates is found to be directly related to photoluminescence emission with energy lower than that present in the PZT with cube-like morphology that emits in 560 nm. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: PZT; Photoluminescence; Microwave hydrothermal synthesis